Pengaruh Tradisi Puja Bhakti Keliling terhadap Keaktifan Umat Buddha dalam Kegiatan Keagamaan di Desa Sumogawe - Ruwadi Ruwadi (Jurnal Budi Pekerti Agama Buddha, 2025)
Local religious traditions play a crucial role in maintaining spirituality, cultural identity, and social cohesion within communities, particularly in rural areas that continue to uphold traditional values. This study aims to examine in depth the influence of the Puja Bhakti Keliling tradition on the level of participation of Buddhist devotees in various religious activities in Sumogawe Village. The study employs a quantitative approach with an associative design, involving 60 purposively selected respondents, and the data were analyzed using simple linear regression. The findings indicate that this tradition contributes significantly to the active engagement of the devotees, with an R² value of 0.634 and a regression coefficient of 0.756, confirming its positive effect. Dimensions of togetherness, social interaction, and spiritual meaning were identified as the main factors driving active participation. The results also reveal low participation in Dhamma learning sessions, highlighting the need for innovation in educational methods and more engaging learning approaches within lay communities. The Puja Bhakti Keliling tradition has proven to serve as a spiritual, social, and educational medium that holistically supports community resilience and the sustainability of religious practices. This study recommends strengthening this traditional model through intergenerational support, innovative participatory learning methods, and contextual approaches that align with community needs.